Systemic Optimization of Legume Nodulation: A Shoot-Derived Regulator, miR2111 - Okuma, Nao; Kawaguchi, Masayoshi (Frontiers in Plant Science, 2021)
Long-distance signaling between the shoot and roots of land plants plays a crucial role in ensuring their growth and development in a fluctuating environment, such as with soil nutrient deficiencies. MicroRNAs (miRNAs) are considered to contribute to such environmental adaptation via long-distance signaling since several miRNAs are transported between the shoot and roots in response to various soil nutrient changes. Leguminous plants adopt a shoot-mediated long-distance signaling system to maintain their mutualism with symbiotic nitrogen-fixing rhizobia by optimizing the number of symbiotic organs, root nodules. Recently, the involvement and importance of shoot-derived miR2111 in regulating nodule numbers have become evident. Shoot-derived miR2111 can systemically enhance rhizobial infection, and its accumulation is quickly suppressed in response to rhizobial inoculation and high-concentration nitrate application. In this mini-review, we briefly summarize the recent progress on the systemic optimization of nodulation in response to external environments, with a focus on systemic regulation via miR2111.